2020
DOI: 10.2460/ajvr.81.11.888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of jejunal microvasculature of healthy anesthetized dogs with sidestream dark field video microscopy

Abstract: OBJECTIVE To determine the feasibility of sidestream dark field (SDF) video microscopy for the evaluation of the jejunal microvasculature of healthy dogs. ANIMALS 30 healthy sexually intact female shelter dogs anesthetized for ovariohysterectomy. PROCEDURES Preoperative physical and clinicopathologic assessments were performed to confirm health status. Then healthy dogs were anesthetized, and the abdomen was incised at the ventral midline for ovariohysterectomy and jejunal microvasculature evaluation. An S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The jejunal antimesenteric border of 30 sexually intact, healthy female dogs weighing >15 kg and undergoing surgery for a routine ovariohysterectomy was interrogated using SDF videomicroscopy as previously described 19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The jejunal antimesenteric border of 30 sexually intact, healthy female dogs weighing >15 kg and undergoing surgery for a routine ovariohysterectomy was interrogated using SDF videomicroscopy as previously described 19 …”
Section: Methodsmentioning
confidence: 99%
“…17,18 Moreover, use on the jejunum of healthy dogs has previously been described and quantitative parameters established. 19 As far as the authors are aware, use on diseased or devitalized canine intestine has not been reported previously. Moreover, although subjective assessment of the effect of sutured enterectomy techniques on the vascular supply has been reported, 10 there is a paucity of data evaluating the effect of staples on the vascular supply, and a quantitative comparison between sutured and stapled enterectomies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human patients; measurements of microvascular flow index have been shown to be similar between bowel and sublingual microvasculature ( de Bruin et al, 2016 ). In veterinary species, sidestream dark field video microscopic assessment of jejunal eGlx has been proposed as a marker of jejunal microvascular health in dogs ( Mullen et al, 2020 ), with potential applications that include aiding in the identification of compromised intestine requiring resection. Measurements in all studies in veterinary species were reported to be similar to those obtained in humans.…”
Section: Visualisation Of the Eglxmentioning
confidence: 99%
“…These include transmission electron microscopy, (58-60) intravital microscopy, (61,62) microparticle image velocimetry, (63) confocal laser scanning microscopy or atomic force microscopy, (10) twophoton laser scanning microscopy, (64) and videomicroscopy using handheld devices and various imaging technologies (i.e., orthogonal polarization spectroscopy, sidestream dark-field imaging incident dark-field imaging) (56). More recently, in vivo indirect assessments of the glycocalyx have been performed in humans and small animals using the sidestream darkfield microscopic technique in conjunction with specialized, proprietary software that measures the width of the vessel lumen available for red blood cell movement as an indirect assessment of glycocalyx thickness (also known as the perfused boundary region or PBR) (65)(66)(67)(68). If there is damage to the ESL, RBC are able to penetrate further toward the endothelium and the PBR increases (69).…”
Section: Monitoring Of the Microcirculation Vs Macrocirculationmentioning
confidence: 99%